Rosavin exerts an antitumor role and inactivates the MAPK/ERK pathway in small-cell lung carcinoma in vitro - Liu Rui; Jiang Cuihong; Zhao Zhizheng; Lv Yutong; Wang Gaoxing (Acta Pharmaceutica)
This study attempts to explore the function and mechanism of action of rosavin in small-cell lung cancer (SCLC) in vitro. The viability and clone formation of SCLC cells were assessed using cell counting kit-8 and colony formation assays, respectively. Apoptosis and cell cycle were detected using flow cytometry and cell cycle analysis, respectively. Wound healing and transwell assays were performed to evaluate the migration and invasion of SCLC cells. Besides, protein levels of p-ERK, ERK, p-MEK and MEK were determined using Western blot analysis. Rosavin repressed the viability and clone formation of SCLC cells, and promoted apoptosis and G0/G1 arrest of SCLC cells. At the same time, rosavin suppressed migration and invasion of SCLC cells. Moreover, protein levels of p-ERK/ERK and p-MEK/MEK were decreased after rosavin addition in SCLC cells. Rosavin impaired malignant behaviors of SCLC cells, which may be associated with inhibition of the MAPK/ERK pathway in vitro.